Study On Structure Performance Of Inhouse Non-Destructive Unit System - Husny, Muhammad Ashraff (Universiti Sains Malaysia, 2020)
This research is to study the structure performance of NDT machine prototypes available in the lab. When the NDT machine prototype is running, it produces vibration to the rotation of the motor. This study is to determine the reliability of the structure of the NDT machine prototype as it may affect the reading of the measurement due to the interference of vibration coming from the motor. Initially, a vibration analysis will be done in the lab but due to the COVID-19 lockdown, the analysis will be done using ANSYS software. The findings also show the necessity for adjustments of the parameters of the NDT machine prototype in the future based on the results from this study.